Strategi Transformasi Digital Dinas Komunikasi dan Informatika Kabupaten Solok: Rencana Lima Tahun ke Depan - Defni Albar; Syafwandi Syafwandi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Digital transformation is a strategic step to improve the quality of public services, bureaucratic efficiency, and transparency in government administration. The Solok Regency Communication and Information Agency considers it necessary to have a five-year medium-term strategy to guide the development of technological infrastructure, information systems, and human resource capacity building. This study aims to formulate a targeted, measurable digital transformation strategy that is in line with the local government's vision. The methods used include needs analysis, evaluation of existing conditions, interviews with stakeholders, and comparative studies of best practices in other regions. The study results indicate the need to strengthen infrastructure networks, integrate electronic-based service systems, develop regional data centers, improve public digital literacy, and strengthen regulations and information security governance. The resulting strategy is expected to serve as a roadmap for the implementation of digital transformation in Solok Regency, which is adaptive to technological developments and capable of addressing the challenges of the digital era. With the implementation of this strategy, Diskominfo is expected to realize fast, accurate, and transparent public services, as well as increase community participation in the use of information technology.